2017
DOI: 10.1590/1678-457x.31816
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary as natural antioxidant to prevent oxidation in chicken burgers

Abstract: Rosemary (Rosmarinus officinalis) is known for their sensory characteristics and antioxidant properties, mainly due to the presence of several phenolic compounds. The aim of this work, was determine the antioxidant activity and apply the Rosemary lyophilized extract (RLE) in chicken burger, for assess their ability to reduce the lipid oxidation. Total antioxidant capacity and phenolic compounds profile were analyzed by colorimetric tests and liquid chromatography analysis, respectively. Thiobarbituric acid rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
1
45
1
2
Order By: Relevance
“…Numerous studies have indicated that antioxidants are useful compounds to reduce lipid oxidation [105]. Many types of plants that naturally contain antioxidants (polyphenols), such as grape seeds, are used as a source of antioxidant incorporated in food products [106], as well as ginger [107], rosemary [108], cinnamon [109], nutmeg [110][111][112], ginger [113] and galangal [114]. The antioxidant activity of spices has been studied as potential and additional sources of natural antioxidants.…”
Section: Natural Antioxidants In Spices Can Inhibit Oxidationmentioning
confidence: 99%
“…Numerous studies have indicated that antioxidants are useful compounds to reduce lipid oxidation [105]. Many types of plants that naturally contain antioxidants (polyphenols), such as grape seeds, are used as a source of antioxidant incorporated in food products [106], as well as ginger [107], rosemary [108], cinnamon [109], nutmeg [110][111][112], ginger [113] and galangal [114]. The antioxidant activity of spices has been studied as potential and additional sources of natural antioxidants.…”
Section: Natural Antioxidants In Spices Can Inhibit Oxidationmentioning
confidence: 99%
“…The analysis of phenolic compounds in rosemary and sage extract through high performance liquid chromatography was carried out using a Dionex Ultimate 3000 (Dionex, Idstein, Germany) system chromatograph including an colunn (Acclaim ® 120 C18) at 40 °C with and a photodiode array detector (HPLC/PDA). The condition of mobile phases were carried out according to Pereira et al [1] and the data analysis were processed with Chromeleon software. Extracts were filtered through a 0.22 µm filter nylon syringe (Millipore, São Paulo, Brazil) and the injection volume was 10 µL with a flow rate of 1.0 mL min -1 .…”
Section: Preliminary Chromatographic Analyses Of Phenolic Compoundsmentioning
confidence: 99%
“…In fact, the rosemary essential oil and lyophilized rosemary extract exhibited an excellent inhibitory effect on lipid oxidation of pork sausage with high acceptance rate [2]. In another study, Pereira et al [1] reported that the rosemary extract had strong anti-oxidative effects in chicken burgers at 21 days of storage at refrigerated temperature. In addition, according to Estevéz et al [4], a mix of sage and rosemary essential oils inhibited oxidative deterioration of liver pâtés to a higher extent than BHT did.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] Lipophilic derivatives of phenolic compounds generally maintain their antioxidant activity and, in some cases, exhibit novel bioactivities that are not found in the original phenolic compounds. [16][17][18] To potentiate the use of polyphenolic antioxidants from natural sources, in addition to the extraction and purification of these compounds, it is necessary to use a process that separates the aglycones (more apolar) from the carbohydrates, such as acid hydrolysis. Acid hydrolysis is a chemical reaction in which an organic molecule undergoes decomposition caused by water, where the acid acts as a catalyst.…”
Section: Introductionmentioning
confidence: 99%